The Dera Heterotopia: Meaning of Home for the Hijra Community (MIST International Journal of Science and Technology, 2025)
The hijra community, representative of third gender individuals, is one of the most deprived communities in Bangladesh. Not conforming to traditional gender binary identities, they do not embrace the conventional notion of family and home. In this context, the study is exploratory research that delves into the realm of hijras, observing their relationship with their dwelling spaces and seeking how they negotiate the meaning of home. By examining hijra dwellings called deras, it aims to understand the dynamics of the hijra lifestyle and ultimately uphold their lived experiences against a dehumanized image of them in the context of Dhaka. For this purpose, the study employs a qualitative approach, drawing on everyday narratives gathered through interviews, group discussions, and observations. Applying Rapoport’s framework for linking the built environment with culture and lifestyle, the paper uncovers the meanings of dera at three levels: at the lower level, it finds that dera provides everyday shelter and a new purpose to these outcasts against the hostile world. At mid-level, the deras become a locus of fostering social relations and a spatial manifestation of hijra existence. And finally, the higher-level meanings reveal a constant juxtaposition of loss and belonging, colourful appearances with feelings of estrangement, and initiation of hijra life with the constant desire for a normal one, making dera a ‘heterotopic space’ a manifestation of the otherness, as per Foucault’s concept of another place. The findings of the paper deepen our understanding of how individuals navigate the oppression of stigma and marginality while actively shaping and transforming their identities in adverse circumstances. It uncovers important relationships between (marginal) community and (housing) environment that can contribute to potential future research within the discourse of spatial justice. The study, by upholding marginal voices of hijra population around everyday space, advocates for their right to the city.MIJST, V. 13,December 2025: 97-110https://doi.org/10.47981/j.mijst.13(02)2025.532(97-110)